2021
DOI: 10.1111/imr.12993
|View full text |Cite
|
Sign up to set email alerts
|

Who am I? (re‐)Defining fibroblast identity and immunological function in the age of bioinformatics

Abstract: leagues 2 highlight the extraordinary advances made possible in this field through the strategic use of gene-targeting and lineage-tracing mouse models, and more recently by single-cell transcriptomics. An array of Cre-reporter mice and mice with inducible expression of Cre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Given the data showing that CAF contribute to regulating tumor immunity (11,12,48), we investigated the different ligands expressed by CAF populations found in human NSCLC (Fig. 4A).…”
Section: Adh1b + Caf and Fap + Caf Correlate With Immune Cell Composi...mentioning
confidence: 99%
“…Given the data showing that CAF contribute to regulating tumor immunity (11,12,48), we investigated the different ligands expressed by CAF populations found in human NSCLC (Fig. 4A).…”
Section: Adh1b + Caf and Fap + Caf Correlate With Immune Cell Composi...mentioning
confidence: 99%
“…When it starts, ECCs possibly expose on the surface adhesion molecules, such as cadherins, integrins, connexins, and others [36] and their contact with neighboring cells and immune cells and CAFs form, possibly, synapse-like connections. Physical cell-cell communication between fibroblasts and other cell types can influence their chemical communication with immune cells [36,124]. There is only indirect evidence for the formation of synapse-like structures between CAFs and cancer and immune cells.…”
Section: Fibroblasts Immune and Cancer Cells Interactionsmentioning
confidence: 99%
“…For example, proin ammatory broblasts are consistently detected across many mouse and human diseases from keloid lesions 18 to aged skin 19 , brotic Dupuytren's nodules 20 , and atopic dermatitis 12 . Functionally, these cells modulate the immune response via production of proin ammatory cytokines 3,[21][22] . Single cell RNA-seq studies have also reported transcriptional differences between broblasts taken from different wound regions 6,9,23 .…”
Section: Introductionmentioning
confidence: 99%